Upaya Peningkatan Pengetahuan Ibu Nifas tentang Kandungan Daun Kelor (Moringa Oleifera) sebagai Pelancar Asi - Pratiwi, Yopi Suryatim; Handayani, Sri; Fatmawati, Nurul (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The Infant Mortality Rate (IMR) in Indonesia is still high. The infant mortality rate is largely due to nutritional factors. Exclusive breastfeeding can reduce infant morbidity and mortality. The most common reason found in breastfeeding mothers who stop breastfeeding is due to insufficient milk production. Utilization of plants/vegetables that function as galactogogue can be used as an alternative to increase milk production. Moringa leaves are one of the plants that people often use to increase milk production. Based on this, it is necessary to carry out health education about the content of Moringa leaves (Moringa Oleifera) as a breast milk booster. The purpose of health counseling is to increase the knowledge of postpartum mothers about the content of Moringa leaves as a breast milk booster. This health education activity was carried out on August 27 2022 in Jempong Baru Village, Sekarbela District, Mataram City. The method used in this devotional activity is using the lecture method, and for the media, namely the media using power point and leaflets. Posttest results obtained by postpartum mothers experienced an increase in knowledge after being given health education about the content of Moringa leaves as a breast milk booster. After the service activities, postpartum mothers are expected to be able to use Moringa leaves as an alternative in improving the smoothness of breastfeeding